Juridical Study of the Supervisory Authority over the Implementation of Nagari Customs and Culture by Traditional Nagari Communities in West Sumatra Province - Pebrihariati. R, Sanidjar; Desmal Fajri; Oksidelfa Yanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
In Article 18B paragraph (2) of the Amendment to the 1945 Constitution, it is stated that "the State recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are regulated in law." In 2018, West Sumatra Province established West Sumatra Province Regional Regulation Number 7 of 2018 concerning Nagari. Problem formulation: 1) What are the consequences of the authority of the Nagari Traditional Council (KAN) after the enactment of West Sumatra Province Regional Regulation Number 7 of 2018 concerning Nagari in West Sumatra Province? 2) What are the legal impacts of supervisory authority on the implementation of nagari customs and culture by the Nagari Traditional Council in West Sumatra Province? The type of research used is normative legal research, using secondary data sources consisting of Primary Legal Materials and Secondary Legal Materials, data collection techniques using document studies, the data is then analyzed using qualitative analysis. Research Results and discussion: 1) Based on the provisions in Article 5 of the West Sumatra Province Regional Regulation Number 7 of 2018 concerning Nagari, the Nagari Institution consists of: a. Nagari Traditional Density; b. Nagari Government; and c. The Nagari Customary Court, one of the authorities of the Nagari Customary Court is: Supervising the Implementation of Nagari Customs and Culture. 2) In the provisions of Article 17 of West Sumatra Province Regional Regulation Number 7 of 2018 concerning Nagari, it states that: The Governor carries out general guidance and supervision over Nagari in the administration of government based on Customary Law. Keywords: Supervision, Authority, Nagari Community.